A Thermosetting Oil for Droplet‐Based Real‐Time Monitoring of Digital PCR and Cell Culture. (6th August 2018) - Wu, Wenshuai; Zhou, Shufang; Hu, Jiumei; Wang, Guoping; Ding, Xiong; Gou, Tong; Sun, Jingjing; Zhang, Tao; Mu, Ying
Abstract: Real‐time observation of small volumes helps to understand phenomena ranging from reaction kinetics to cellular heterogeneity. However, high‐throughput real‐time monitoring systems based on droplets are rarely reported due to droplet motion and coalescence. Herein, a thermosetting oil is developed as a continuous phase to solve these problems through transforming into elastic solid after droplet generation. The thermosetting oil consists of silicon oil, nonionic surfactant, vinyl silicone oil, hydrosilicone oil, and Pt catalyst. Using Pt as the catalyst, the polymerization of this mixture can be accomplished in 72 min and 37 s at 37 and 95 °C, respectively, based on the hydrosilation of vinyl silicone oil and hydrosilicone oil without other inducers (e.g., UV, Ca 2+ ). Droplet‐based real‐time monitoring of digital polymerase chain reaction (PCR) and cell culture is successfully achieved using this thermosetting oil, demonstrating that droplets motion and coalescence can be eliminated by the crosslinking material without the influence on bioreactions. In addition, the PCR products can be totally recovered from microcapsules created by this oil for further analysis. Thus, the newly developed oil allows real‐timely monitoring individual droplets in a high‐throughput manner, as well as has potential for other bioreactions and cell‐based assays. Abstract : A thermosetting oil is developed as a continuous phase to produce monodisperse droplets using microfluidic droplet technology. Based on hydrosilation, this curable material can polymerize spontaneously using Pt as catalyst, resulting in immobile droplets and eliminating droplet coalescence. Being biocompatible and gas permeable, this liquid is applied to droplet‐based real‐time monitoring of digital PCR and cell culture.